Periodization in team sport games - A review of current knowledge and modern trends in competitive sports - Lyakh, V.; Mikolajec, K.; Bujas, P.; Witkowski, Z.; Zajac, T.; Litkowycz, R.; Banys, D. (Journal of Human Kinetics, 2016)
The main goal of this study was to present a review of current knowledge and modern trends in periodization of the training process in team sports. The research objectives were: an analysis of various aspects of periodization of the annual training cycle for elite athletes practicing team sport games, an attempt to determine both the examined and unexamined issues related with periodization of training as well as to indicate directions for further research, and finally, presentation of different training loads and competitions in micro-, meso- and macrocycles. The research consisted of the analysis and generalization of the bibliography, methods of monitoring training and competition loads of the Polish national U17 female soccer team in the seasons 2011/2012 and 2012/2013, as well as of the female basketball division one club in the season 2014/2015. Findings of the present study indicate resolved as well as unresolved aspects of annual training cycle periodization in team sport games and provide information on the types of training and competitive workload planning in micro-, meso- and macrocycles.